2017
DOI: 10.1074/jbc.m116.753632
|View full text |Cite
|
Sign up to set email alerts
|

Decorin-inducible Peg3 Evokes Beclin 1-mediated Autophagy and Thrombospondin 1-mediated Angiostasis

Abstract: We previously discovered that systemic delivery of decorin for treatment of breast carcinoma xenografts induces paternally expressed gene 3 (Peg3), an imprinted gene encoding a zinc finger transcription factor postulated to function as a tumor suppressor. Here we found that de novo expression of Peg3 increased Beclin 1 promoter activity and protein expression. This process required the full-length Peg3 as truncated mutants lacking either the N-terminal SCAN domain or the zinc fingers failed to translocate to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 121 publications
(135 reference statements)
0
52
0
Order By: Relevance
“…Both the core protein of decorin, especially the LRR domain, and the GAG side chain enable decorin to bind and sequester a large number of different molecules. These decorin‐interacting partners encompass versatile molecular categories including ECM macromolecules, growth factors and some of their receptors, cytokines, enzymes, hormones and lipoproteins (Figure ) (Yamaguchi et al, ; Bi and Yang, ; Gubbiotti et al, ; Torres et al, ). These interactions form the basis of decorin's multifaceted functions.…”
Section: Decorin – Structure Interactions and Functionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Both the core protein of decorin, especially the LRR domain, and the GAG side chain enable decorin to bind and sequester a large number of different molecules. These decorin‐interacting partners encompass versatile molecular categories including ECM macromolecules, growth factors and some of their receptors, cytokines, enzymes, hormones and lipoproteins (Figure ) (Yamaguchi et al, ; Bi and Yang, ; Gubbiotti et al, ; Torres et al, ). These interactions form the basis of decorin's multifaceted functions.…”
Section: Decorin – Structure Interactions and Functionsmentioning
confidence: 99%
“…Regarding intestinal homeostasis, it was shown that decorin expression is vital for the maintenance of cell maturation (Bi et al, ). During tumourigenesis, decorin was further shown to be a regulator of the innate immune system (Merline et al, ; Frey et al, ), autophagy (Torres et al, ) and mitophagy (Buraschi et al, ), as discussed in more detail below. Although most of decorin's interactions are mediated via its core protein, the GAG side chain is also of great importance (Järvinen and Prince, ; Neill et al, ).…”
Section: Decorin – Structure Interactions and Functionsmentioning
confidence: 99%
See 3 more Smart Citations